MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN TEATER DI KELAS XI.F3 SMA NEGERI 2 BATANG ANAI - Hilda Ismia Putri; Yuliasma (Universitas Negeri Padang, 2025)
This study aims to reveal and describe the improvement of student learning outcomes using audio-visual media in theatre learning in class XI.F3 at SMA Negeri 2 Batang Anai. This research is a classroom action research conducted in 2 cycles with stages of planning, implementation, observation and reflection. Data were collected through literature review, observation and documentation. Research instruments consisted of observation sheets and student learning outcome sheets. The data were analysed using percentage formulas. The results showed that the use of audio-visual media in theatre learning was able to significantly improve student learning outcomes. This improvement occurred because audiovisual media helped visualise abstract material, increased students' interest and participation, enhanced contextual understanding and encouraged active and collaborative learning. Student learning activities in cycle I achieved an average score of 56% and increased in cycle II to 85% with a very good category. The results of cognitive test assessments in cycle I showed that only 37% of students achieved the completion score, whereas in cycle II there was an improvement with 92% of students meeting the completion score according to the school's KKTP standard. The improved cognitive test results in cycle II reached 72.8, with 13 out of 20 students (65%) meeting the Minimum Mastery Criterion (KKM) set, which is 70.